Procoagulant and Anticoagulant Factors in Childhood Hypothyroidism. (14th May 2012) - Kilic, Nevin; Dallar, Yildiz; Simsek, Enver; Karamercan, Sirma; Tapci, Ayse Esra; Alioglu, Bulent
Abstract : The aim of this study was to investigate the effects of thyroid hormone deficiencies in childhood on the elements of coagulation proteins. Consecutive 54 children with hypothyroidism and 55 healthy controls aged 1 month–16 years were enrolled. One year after Na-L-thyroxine treatment, the study parameters were reevaluated. Thyroid function tests, procoagulant and anticoagulant proteins were performed for children with hypothyroidism and healthy controls. Significant decreased results were found in children with hypothyroidism in terms of fibrinogen, TT, and anticoagulant proteins including AT, PC, PS, and fPS. Significant increases were found with respect to APTT, fibrinogen, and TT. In the evaluation of posttreatment changes a statistically significant increase was found in vWF, FVIII, AT, PC, PS, and fPS. A positive correlation was found between fT4 and vWF, FVIII, PC, and PS. We would like to emphasize that the coagulation system especially vWF and FVIII, and particularly the anticoagulant system, should be monitored closely in patients followed up for hypothyroidism. Thyroid hormones should be examined and, if necessary, hormone replacement therapy should be administered in patients followed up for a predisposition to coagulation. Additionally, further studies with larger series are needed to investigate the effects of hypothyroidism on the coagulation system.